6 weeks consumption of pure fresh coconut milk caused up-regulation of eNOS and CSE protein expression in middle-aged male rats - Chaweewan Jansakul; Jomkarn Naphatthalung; Sakda Pradab; Somruedee Yorsin; Kanyanatt Kanokwiroon (Universidade de São Paulo, 2018)
Coconut milk (CCM) has been an important cooking ingredient in the Asia-Pacific region since ancient time. Due to its high content of saturated fatty acids, it has been considered atherogenic. We have tested if chronic consumption of fresh coconut milk by middle-aged male rat affects vascular function, plasma glucose and lipid profiles. Compared to control, CCM caused lower maximal contraction to phenylephrine of thoracic aortic rings and increased relaxation to acetylcholine that was abolished by N G-nitro-L-arginine (L-NA) or disruption of the endothelium. DL-propargylglycine caused slight increase in baseline tension of L-NA treated aortic rings of CCM-treated rats and produced higher contractile response of the aortic rings to low concentrations of phenylephrine. The aortic eNOS- and cystathionine-γ-lyase(CSE) proteins expression of the CCM-treated rats were also higher than in controls. Except for lower fasting plasma glucose there were no changes in blood chemistry for the CCM treated rats. CCM consumption caused up-regulation of eNOS and CSE protein expression which resulted in increased production of NO and H2S from the blood vessels with attenuation of vasocontraction to phenylephrine and increased relaxation to acetylcholine. These novel benefits may be expected to reduce the development of cardiovascular risk factors in the aging rat.